Compatible deformation and extra strengthening by heterogeneous nanolayer composites. (1st April 2020) - Li, Jianjun; Lu, Wenjun; Gibson, James; Zhang, Siyuan; Korte-Kerzel, Sandra; Raabe, Dierk
Abstract: A topologically heterogeneous microstructure design is introduced in a Cu/Zr nanolayered composite, in which each soft 100 nm Cu or Zr layer is surrounded on both sides by several hard 10 nm Cu/Zr bilayers. This design aims to impose a full geometrical constraint on all of the soft layers. Micropillar compression tests demonstrate that the composite deforms in a compatible fashion among the layers, in which no extrusion of the soft layers occurs. An elevated strength of 730 MPa is achieved in the composite compared with the strength prediction based on the linear rule of mixtures. Graphical abstract: The newly-designed heterogeneous Cu/Zr layered sample shows compatible deformation without extrusion of soft Cu layers (a, b), whereas the homogeneous sample exhibits obvious extrusions even under much smaller applied strain (see arrows in c, d). Scale bar: 200 nm. Image, graphical abstract